Linkage to care and treatment among men with reactive HIV self-tests after workplace-based testing in Uganda: A qualitative study - Muwanguzi, Patience A.; Nelson, LaRon E.; Ngabirano, Tom D.; Kiwanuka, Noah; Osingada, Charles Peter; Sewankambo, Nelson K. (Frontiers in Public Health, 2022)
Introduction HIV self-testing at workplaces has the potential to reach men at risk of HIV infection with lower access to HIV testing services. While several studies have reported high uptake of HIV self-testing, linkage to HIV care following a positive result remains a challenge. This study, therefore, explored the motivators for and barriers to linkage to HIV care and treatment among men who returned positive results following workplace-based HIV self-testing. Methods A qualitative descriptive study, among men in private security services in Kampala district, Uganda. The men were eligible to participate if they were aged 18 to 60 years and had worked at the company for more than 6 months. Following HIV self-testing, participants with reactive (positive) self-test results were purposively sampled and engaged in key informant interviews. Inductive content analysis was employed to identify the motivators and barriers to the men's linkage to HIV treatment and care. Results Overall, 12 men participated in the study, of whom 9 (75%) were security guards, and the rest held management positions. The motivators for linkage to care coalesced under five categories. (i) Communication (open communication, phone reminders, consistent communication) (ii) Navigating health facility systems and processes (enabling health facility environment, easy access to health care, employing ART clinic counselors as part of the study team, health workers) (iii) Linkage support (linkage companions, referral forms, linkage facilitation, individualized linkage plan, pre-arranged clinic appointments) (iv) Psychosocial support (counseling sessions, family support, online and social media support, peer support) (v) workplace environment (employer's support, work schedules and policies). The barriers to linkage to HIV care included (i) Inflexible work schedules, (ii) Far distances to travel to access ART (iii) mandatory work transfers, (iv) disruptive effects of the COVID-19 pandemic, (v) Denial of HIV-positive results and (vi) fear of stigma and discrimination at health facilities. Conclusion The findings suggest the need for innovative interventions to facilitate regular follow-up and open communication with workplace-based HIV self-testers, to improve linkage to HIV care and treatment. Furthermore, initiating linkage plans during pre-test counseling and working in collaboration with health facilities and clinics may improve linkage to care.